Pengaruh Kualitas Pelayanan Terhadap Loyalitas Nasabah Jasa Asuransi Pada Pt. Asuransi Askrida Syariah Banjarmasin - Ihya Ulumiddina (BIMA: Jurnal Bisnis dan Manajemen, 2022)
This study aims to determine the effect of service quality (X1) simultaneously, partially and dominantly on customer loyalty insurance services at PT. Banjarmasin Sharia Askrida Insurance. This study uses a quantitative type of research. The population in this study was 1300 people. Sampling using the solvin method as many as 100 respondents. Collecting data using questionnaires, observations, and interviews. The data analysis technique used is multiple linear regression analysis using SPPS software version 20 for windows. The results showed that (1) the service quality variable had a simultaneous effect on changes in the customer loyalty variable (Y) was 79% while the remaining 21% was influenced by other factors not included in the scope of research at PT. Banjarmasin Sharia Askrida Insurance. (2) the service quality variable has a partial effect on customer loyalty in insurance services at PT. Askrida Syariah Banjarmasin Insurance with a Tangible variable T value (X1) of 2.048, Reliability (X2) of 2.280, Responsiveness (X3) of 2.014, Assurance (X4) of 0.542, Empathy (X5) of 6.318. (3) among the service quality variables the most dominant is the empathy variable (X5) with the largest regression coefficient value of 0.519 or 51.9%.